Global warming and the future of the earth - Watts, Robert G. (Synthesis lectures on energy and the environment, technology, science, and society, 2007)
"The book begins with the important distinction between weather and climate, followed by data showing how carbon dioxide has increased and the incontrovertible evidence that it is caused by burning fossil fuels (i.e., coal, oil, and natural gas). The author also addresses the inevitable skepticism that global warming arouses and offers a number of responses to the global warming skeptics. After dealing with the skeptics, the author analyzes both the current and future effects of global warming. These future effects are based on scenarios or "storylines" put forth by the International Institute for Applied Systems Analysis. In closing, the author addresses the controversial (and grim) suggestion that we have already passed the "tipping point, "which is the time after which, regardless of our future actions, global warming will cause considerable hardship on human society."--Book jacket.